2021
DOI: 10.1111/bju.15389
|View full text |Cite
|
Sign up to set email alerts
|

Rising incidence rates and unaltered survival rates for primary upper urinary tract urothelial carcinoma: a Dutch population‐based study from 1993 to 2017

Abstract: To assess trends in the incidence, disease management and survival rates for upper urinary tract urothelial carcinoma (UTUC) in the Netherlands. Materials and methodsPatients diagnosed with primary UTUC in the Netherlands between 1993 and 2017 were identified through the populationbased Netherlands Cancer Registry (NCR). Patient and tumour characteristics, as well as information on treatment and vital status, were retrieved from the NCR. Age-standardized incidence rates were calculated, stratified by age, gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…The present study showed that the stable annual age‐standardized incidence of UTUC was similar to those reported in Asian countries 5,9 and the USA, 3 but different from other European countries 6,7 and another report from Taiwan 17 . Besides comparability due to different definitions of UTUC, 17 the most recent study highlights that the wide range of imaging applications used for UTUC diagnosis might bring substantial increases in the incidence and diagnosis at different TNM stages 6 . It is worth examining how imaging usage trends affect the current trend in UTUC occurrences and prognosis, particularly in Asian countries.…”
Section: Discussionsupporting
confidence: 62%
“…The present study showed that the stable annual age‐standardized incidence of UTUC was similar to those reported in Asian countries 5,9 and the USA, 3 but different from other European countries 6,7 and another report from Taiwan 17 . Besides comparability due to different definitions of UTUC, 17 the most recent study highlights that the wide range of imaging applications used for UTUC diagnosis might bring substantial increases in the incidence and diagnosis at different TNM stages 6 . It is worth examining how imaging usage trends affect the current trend in UTUC occurrences and prognosis, particularly in Asian countries.…”
Section: Discussionsupporting
confidence: 62%
“…Although we did not perform a competing risks survival analysis, when comparing overall survival to cancer-specific survival, the proportion of noncancer-related deaths are appreciable, likely reflecting comorbid conditions and the advanced age of our patient population. As epidemiologic data have suggested a subtle but demonstrable increase in UTUC incidence in recent years, an increase in highly lethal advanced disease, and a relative stagnation of survival outcomes, these findings on the whole highlight the need for advancing effective and cost-contained management strategies ( 2 , 4 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial cell carcinoma of the upper tract (UTUC) is a heterogeneous disease with increased mortality with more advanced stage ( 1 ). Epidemiologic data suggest the incidence of UTUC is rising, whereas survival remains relatively unchanged ( 2-4 ). Management of patients with UTUC is highly variable and depends on a number of factors including presence of a contralateral kidney, baseline renal function, tumor location (renal pelvis vs ureter), size, grade, clinical stage, and focality ( 5 ).…”
mentioning
confidence: 99%
“…Recent studies have focused on the genetic features of UTUC using next-generation sequencing and identified different molecular classifications with distinct clinical behaviors [5][6][7]. However, despite the refinement of the surgical and medical management of UTUC, patient outcomes have not changed significantly over the past few decades [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the world's population is aging, and UTUC is associated with older age, with a peak incidence in people in their 70s and 80s, and with a high prevalence of comorbidities [2,3,8,9]. Comorbidity is defined as any coexisting condition or disease that can affect the diagnosis, treatment, and prognosis of an index disease under study [10,11].…”
Section: Introductionmentioning
confidence: 99%